TINJAUAN YURIDIS PEMBAGIAN WARIS TERHADAP ANAK ALM. IVAN LIMBUNAN BERDASARKAN PUTUSAN PENGADILAN - Rasyaki Putri Adim; Khairani Bakri (Fakultas Hukum Universitas Trisakti, 2022)
Children from the first, second, third, fourth, and fifth marriages of the late Ivan Limbunan experience challenges of disagreements related to inheritance distribution. The roblem: what is the content of Makassar District Court Decision No. 422/Pdt.G/2020/PN.MKS and how is inheritance distributed to the offspring of the late Ivan Limbunan's first, second, third, fourth, and fifth marriages in accordance with the Civil Code? According to the Civil Code, Part Number 1 Concerning Distribution of the late. Ivan Limbunan's Inheritance to His Heirs is appropriate or not. This article uses secondary data, descriptive analysis, qualitative approach, libraries research. Research findings, analysis, and conclusions; according to Articles 832 and 852 of the Civil Code, the six children from the deceased Ivan Limbunan's first, second, third, fourth, and fifth marriages as well as the Fransiska (8/14) 1/2 the inheritance might all get inheritance. Fill in the Decision of the Makassar District Court Number 422/Pdt.G/2020/PN.MKS Part Number 1 regarding the distribution of the inheritance of the late Ivan Limbunan to his heirs not in accordance with Articles 250, 830, and 852, and Article 852a of the Civil Code. Ivan Limbunan each gets (1/14) share.